Bruce - Terhune, Albert Payson, 1872-1942 (Salt Lake City, UT : Project Gutenberg, 2000)
"Bruce" by Albert Payson Terhune is a novel likely written in the early 20th century. The book centers around the titular character, Bruce, a collie that endures hardship and strives to find acceptance and love from humans in a world that often discriminates against female dogs. The story explores themes of loyalty, companionship, and the challenges faced by animals in a human-dominated society. The opening of "Bruce" introduces the protagonist, a female collie named Rothsay Lass, who is initially overlooked because of her gender despite her exceptional qualities and pedigree. Left alone in a kennel after her siblings are sold, her fate changes when a lonely boy named Dick Hazen comes to the kennel. Their bond grows quickly as he chooses her for his birthday gift. However, Dick's mother disapproves of a female dog, leading to a conflict that empowers Lass to defend her young master. This portion of the book sets the stage for the journey of both the dog and Dick, establishing the emotional depth and challenges they face in their relationship, foreshadowing future adventures and trials. (This is an automatically generated summary.)
Release date is 2000-11-01
Produced by Dianne Bean. HTML version by Al Haines.
Keywords: Dogs -- Juvenile fiction